Cumulative Incidence of SARS-CoV-2 Infections Among Adults in Georgia, United States, August to December 2020. (18th October 2021) - Chamberlain, Allison T; Toomey, Kathleen E; Bradley, Heather; Hall, Eric W; Fahimi, Mansour; Lopman, Benjamin A; Luisi, Nicole; Sanchez, Travis; Drenzek, Cherie; Shioda, Kayoko; Siegler, Aaron J; Sullivan, Patrick Sean
Abstract: Background: Reported coronavirus disease 2019 (COVID-19) cases underestimate true severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Data on all infections, including asymptomatic infections, are needed. To minimize biases in estimates from reported cases and seroprevalence surveys, we conducted a household-based probability survey and estimated cumulative incidence of SARS-CoV-2 infections adjusted for antibody waning. Methods: From August to December 2020, we mailed specimen collection kits (nasal swabs and blood spots) to a random sample of Georgia addresses. One household adult completed a survey and returned specimens for virus and antibody testing. We estimated cumulative incidence of SARS-CoV-2 infections adjusted for waning antibodies, reported fraction, and infection fatality ratio (IFR). Differences in seropositivity among demographic, geographic, and clinical subgroups were explored with weighted prevalence ratios (PR). Results: Among 1370 participants, adjusted cumulative incidence of SARS-CoV-2 was 16.1% (95% credible interval [CrI], 13.5%–19.2%) as of 16 November 2020. The reported fraction was 26.6% and IFR was 0.78%. Non-Hispanic black (PR, 2.03; 95% confidence interval [CI], 1.0–4.1) and Hispanic adults (PR, 1.98; 95% CI, .74–5.31) were more likely than non-Hispanic white adults to be seropositive. Conclusions: As of mid-November 2020, 1 in 6 adults in Georgia had been infected with SARS-CoV-2. The COVID-19 epidemic in Georgia is likely substantially underestimated by reported cases. Abstract : Using data from a probability survey of households in Georgia, United States we estimated that 1.3 million adults aged ≥18 years experienced SARS-CoV-2 infections by 16 November 2020, of whom 1 in 4 were reported and of whom 0.78% died.